Sistem Pendidikan di Singapura - Meta Nopita; Agus Faisal Asyha (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to comprehensively analyze the education system in Singapore through philosophical, historical, legal, geographical, psychological perspectives, formal, nonformal, and informal educational levels, curriculum, teachers, students, and government policies. The study subjects include the entire educational structure in Singapore, encompassing government policies, curriculum, teachers, and students from preschool to higher education. The research was conducted through literature and documentation review, utilizing scientific journals, academic books, institutional reports, and official government documents as data sources. The results indicate that Singapore’s education philosophy emphasizes holistic cognitive, affective, and psychomotor development, supported by government policies such as the Compulsory Education Act 2000 and SkillsFuture programs for integration of formal and nonformal education. Geographical distribution and educational infrastructure support equitable quality education, while an integrated curriculum emphasizing critical thinking, creativity, collaboration, and digital literacy, together with teacher professional development, produces adaptive and innovative learning. Overall, the findings confirm that the synergy among educational philosophy, historical context, regulation, geographical and psychological aspects, curriculum, teachers, students, and government policy forms a comprehensive, adaptive, and sustainable education system in Singapore. This study provides insights for policymakers and educational practitioners to understand the factors contributing to Singapore’s educational success.